2012
DOI: 10.1002/oti.1338
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Depressive Symptoms in an Elderly Mexican‐American Female with Type 2 Diabetes Mellitus: A Single‐Subject Study

Abstract: The purpose of this study was to determine if occupation-based activities improve diabetes self-management and reduce depressive symptoms in an elderly Mexican-American woman with type 2 diabetes mellitus (T2DM). There have been no known studies showing occupational therapy's role in self-care management of T2DM in people with depressive symptoms. The individual in this single-subject research was evaluated using glycosylated haemoglobin blood tests, four self-reported standardized questionnaires, participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…The articles emphasized the competence and capacity of the occupational therapist in the analysis of everyday life, and the exclusive strategies that integrate the guidelines given by several health professionals, with the reality found in the daily life of individuals. [8][9][10][11][12][13][14][15][16]18,21 Address the structure of habits and routines is a specific intervention of Occupational Therapy for any individual who presents a transient or chronic condition that affects performance in daily activities, such as in metabolic, neurological, rheumatologic, and dementia. 22,23 By addressing the routine changes demanded by diabetes, we observed that there is a great impact in several life contexts, what can limit the individual functionality in their participation and performance in daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The articles emphasized the competence and capacity of the occupational therapist in the analysis of everyday life, and the exclusive strategies that integrate the guidelines given by several health professionals, with the reality found in the daily life of individuals. [8][9][10][11][12][13][14][15][16]18,21 Address the structure of habits and routines is a specific intervention of Occupational Therapy for any individual who presents a transient or chronic condition that affects performance in daily activities, such as in metabolic, neurological, rheumatologic, and dementia. 22,23 By addressing the routine changes demanded by diabetes, we observed that there is a great impact in several life contexts, what can limit the individual functionality in their participation and performance in daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is not their responsibility to provide adequate diet, prescription of exercises or medications, but to verify with the patient how this requirements and guidelines will be applied to daily life, and to identify aspects that can be negative and positive to a good adhesion to the guidelines. [8][9][10][11][13][14][15][16]18,21 Most studies present research with lowincome and Latino individuals; it should be considered that this public may present greater difficulties to understand the guidelines given by the professionals and to include such guidelines into their routines, either due to the social environment, the food adequation, the access to medicines or the closest monitoring with health professionals. [8][9][10][11]13,15,18 Another group with limitations to follow guidelines are the elderly, who may need more assistance and follow-up to make lifestyle changes, since adherence in this group is mostly low due to the difficulty of modifying long consolidated habits, which compromises all the proposed treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 There is also a place for single case study research, though not generalizable, it creates deeper understanding of the issues that may prevent adherence for one person or one group at a time. 17,18 I can share that it was my personal experience of living with type one diabetes that best helped me to design and shape experiential programs for individuals 15,16 When first diagnosed, I skipped the hospitalization and the certified diabetes education classes. Instead, I learned about diabetes as a counselor of 5-year-old girls, while living at a residential diabetes summer camp nearby my home.…”
mentioning
confidence: 99%